Ekosistem Manajemen Talenta Dalam Pengelolaan Pengembangan ASN yang Profesional di Kota Bima - Miftahuddin Miftahuddin; Ridwan Ridwan; Musmuliadin Musmuliadin (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
The implementation of talent management is a juridical-strategic instrument to manifest a meritocracy system aimed at achieving the professionalism of the Civil Service Apparatus (ASN). This study aims to analyze regulatory readiness and the institutional policy design of the talent management ecosystem in developing a professional Civil Service Apparatus in Bima City. The research method used is empirical legal research (socio-juridical) focused on the Regional Civil Service and Human Resources Development Agency (BKPSDM) of Bima City. Data collection was conducted through in-depth interviews with key bureaucratic actors, observations, and a study of civil service legal documents. The research findings indicate that as an initial achievement, the Bima City Government has laid the foundation for the merit system, earning a "Good" predicate and initiating a competence-based career profiling program for 495 civil servants. However, during implementation, this ecosystem faces several obstacles, namely the absence of comprehensive local regulations, unintegrated civil service information technology databases, a limited number of assessors, and resistance from conventional work culture. As a policy design recommendation, from a juridical perspective, the formulation of a holistic Bima Mayoral Regulation is required to synchronize the management of the talent pool, alongside the restructuring of BKPSDM into a Talent Development Center. This policy recommendation is expected to offer future implications in ensuring legal certainty, objectivity, and career fairness for the Civil Service Apparatus.